A gradient microarray porous nanosilver column / hydrophobic molecule brush composite SERS substrate for microplastic size retention separation detection and a preparation method and application thereof
Patent Information
- Application Number
- CN202611241945.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-20
AI Technical Summary
[0008]本发明的目的在于提供一种用于微塑料尺寸滞留分离检测的梯度微阵列多孔纳米银柱/疏水分子刷复合SERS基底及其制备方法和应用,以解决现有SERS基底在微塑料混合样品检测中难以兼顾尺寸依赖性滞留、区域富集、信号增强、柱间开放流动空间以及液体界面润湿调控的问题
第一,本发明通过在同一高导电硅片衬底上构建沿流动方向依次减小间距的梯度微阵列区域,使不同粒径微塑料颗粒在流动过程中发生差异化滞留、减速、富集和接触,实现尺寸滞留分离与SERS检测的一体化。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the fields of surface-enhanced Raman scattering (SERS) detection, micro / nanostructure sensing substrates, and environmental microplastic detection technologies. Specifically, it relates to a gradient microarray porous nanosilver column / hydrophobic molecular brush composite SERS substrate for detecting the size retention and separation of microplastics, its preparation method, and its application. Background Technology
[0002] Microplastics are widely found in water, soil, sediments, and organisms, characterized by small particle size, diverse types, complex sources, and strong environmental persistence. With increasing demands for environmental monitoring, higher requirements are being placed on the rapid identification and separation of microplastics of different particle sizes and materials.
[0003] Raman spectroscopy offers advantages such as non-destructive testing, strong molecular fingerprinting capabilities, and applicability to micro-area analysis, making it suitable for identifying microplastic species. However, in real-world mixed samples, microplastic particles of different sizes and materials may coexist. Since microplastic particles are typically on the micrometer scale, their distribution, movement, retention, and contact state on the detection substrate directly affect the Raman signal acquisition. Conventional Raman detection is easily limited by factors such as weak signal strength, difficulty in particle localization, and low detection efficiency.
[0004] Surface-enhanced Raman scattering (SERS) technology can enhance the Raman signal of analytes by generating localized electromagnetic field enhancement effects through noble metal nanostructures. Silver nanostructures, due to their strong plasmon response, are widely used for SERS substrate construction. However, traditional random rough silver films, silver nanoparticle films, or random porous silver substrates primarily provide signal enhancement and are difficult to simultaneously achieve spatial separation, regional enrichment, and in-situ SERS identification of microplastic particles of different sizes.
[0005] On the other hand, while existing microfluidic sieving or microstructure separation methods can sieve particles to a certain extent by utilizing differences in channel size, for microplastic particles, excessively narrow or deep channel structures can easily cause particle blockage, impeded flow of the test liquid, or difficulty in repeatedly locating the detection area. Furthermore, if the microstructure itself lacks effective SERS hotspots, even if particle separation is achieved, it is difficult to perform highly sensitive spectral identification of the retained particles.
[0006] Therefore, there is an urgent need for a composite detection substrate that simultaneously possesses the functions of microplastic size retention and separation, particle regional enrichment, smooth liquid flow, and SERS-enhanced recognition.
[0007] However, in existing surface-enhanced Raman scattering (SERS) detection techniques for microplastics, separation and detection are usually two separate steps, making integrated in-situ analysis difficult. Specifically, while conventional random nanostructured SERS substrates can provide signal enhancement, they cannot spatially separate microplastics of different sizes, leading to signal interference between different particles. Existing microfluidic sieving or membrane separation techniques often employ closed channels or deep-pore structures, which are prone to hard clogging by microplastic particles. Furthermore, sample transfer after separation is required for detection, making the process cumbersome and prone to sample loss. In addition, during the drying process, the capillary film remaining on the substrate surface often drags separated particles, causing disordered migration or aggregation, severely affecting the accuracy and repeatability of the detection. Therefore, there is an urgent need for a composite detection substrate that can simultaneously achieve microplastic size separation, in-situ enrichment, efficient SERS signal reading, and effectively suppress particle drift during the drying process. Summary of the Invention
[0008] The purpose of this invention is to provide a gradient microarray porous nanosilver column / hydrophobic molecular brush composite SERS substrate for the detection of microplastic size retention and separation, as well as its preparation method and application, to solve the problem that existing SERS substrates are difficult to simultaneously achieve size-dependent retention, regional enrichment, signal enhancement, open flow space between columns, and liquid interface wetting control in the detection of microplastic mixed samples.
[0009] This invention first provides a gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate for the detection of microplastic size retention separation, comprising: a conductive substrate, wherein an array of porous silver nanopillars is disposed on the surface of the conductive substrate as a gradient microarray porous silver nanopillar layer; a polydimethylsiloxane-based hydrophobic molecular brush modification layer is disposed on the surface of the porous silver nanopillars; the porous silver nanopillars have nanopores, nano-gap structures and / or nanoparticle connection structures; the nanopores, nano-gap structures and / or nanoparticle connection structures can form a local electromagnetic field enhancement region. According to a preset flow direction of the test liquid, the gradient microarray porous silver nanopillar layer is divided into several sieving regions, and within the same sieving region, the spacing between the porous silver nanopillars is the same; between adjacent sieving regions, the spacing between the porous silver nanopillars upstream is greater than that downstream. The diameter of the porous silver nanopillars is 1–10 μm, and the spacing between adjacent porous silver nanopillars is 1–20 μm.
[0010] Preferably, the porous silver nanopillars are formed from Ag7O8NO3 precursor through reduction treatment to provide surface-enhanced Raman scattering hotspots. The polydimethylsiloxane-based hydrophobic molecular brush modification layer is formed from dimethyldimethoxysilane through a hydrolysis-condensation reaction under acid catalysis. The conductive substrate is a p-type high-conductivity silicon wafer with a resistivity of 0.0005–0.0009 Ω·cm.
[0011] Preferably, the spacing between the porous silver nanoparticles is specifically the edge spacing between any two adjacent porous silver nanoparticles within the same sieving region; the number of sieving regions is three, namely a large-spacing region, a medium-spacing region, and a small-spacing region. The edge spacing between adjacent porous silver nanoparticles in the large-spacing region is 6–15 μm; the edge spacing between adjacent porous silver nanoparticles in the medium-spacing region is 3–8 μm; and the edge spacing between adjacent porous silver nanoparticles in the small-spacing region is 1–4 μm. The large-spacing region serves as the inlet region and / or pre-dispersion region for the test liquid; the medium-spacing region is used to cause larger microplastic particles to be retained, slowed down, enriched, and / or contacted; and the small-spacing region is used to cause smaller microplastic particles that continue to flow with the test liquid to be retained, slowed down, enriched, and / or contacted.
[0012] Preferably, the edge spacing between adjacent porous silver nanopillars in the large-spacing region is 10 μm; the edge spacing between adjacent porous silver nanopillars in the medium-spacing region is 5 μm; and the edge spacing between adjacent porous silver nanopillars in the small-spacing region is 2 μm. The diameter of the porous silver nanopillars is 4 μm. When the edge spacing between adjacent porous silver nanopillars in the large-spacing region, medium-spacing region, and small-spacing region are 10 μm, 5 μm, and 2 μm, respectively, the corresponding center-to-center distances between adjacent porous silver nanopillars are 14 μm, 9 μm, and 6 μm, respectively.
[0013] This invention also provides a method for preparing the gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate, comprising the following steps: S1, a highly conductive silicon wafer is provided as a conductive substrate, and a negative photoresist is coated on the surface of the conductive substrate; S2, The negative photoresist is patterned using a laser direct writing process to form a circular opening array region with different edge spacing in the negative photoresist layer, so that the highly conductive silicon wafer is exposed at the circular openings. S3, using a highly conductive silicon wafer with the circular opening array region as the working electrode, electrochemical growth is carried out in a silver-containing electrolyte to grow the Ag7O8NO3 precursor on the surface of the highly conductive silicon wafer exposed in the circular opening. S4, remove the negative photoresist to obtain a gradient microarray Ag7O8NO3 precursor columnar structure defined by the circular opening array template; S5, the gradient microarray Ag7O8NO3 precursor columnar structure is placed in a reducing agent solution for reduction treatment, so that the Ag7O8NO3 precursor is transformed into gradient microarray porous silver nanopillars. S6, a polydimethylsiloxane-based hydrophobic molecular brush modification layer is formed on the surface of the gradient microarray porous silver nanopillars to obtain the gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate.
[0014] Preferably, in step S6, the method for forming the polydimethylsiloxane-based hydrophobic molecular brush modification layer includes: The gradient microarray porous silver nanopillars were subjected to plasma treatment. The plasma-treated gradient microarray porous silver nanopillars were brought into contact with a reaction solution containing dimethyldimethoxysilane, isopropanol and concentrated sulfuric acid. Dimethyldimethoxysilane undergoes a hydrolysis-condensation reaction on the surface of the gradient microarray porous silver nanopillars under acid catalysis and with the participation of ambient moisture, forming a polydimethylsiloxane-based hydrophobic molecular brush modification layer.
[0015] Preferably, the mass ratio of isopropanol, dimethyldimethoxysilane, and concentrated sulfuric acid in the reaction solution is 10:1:0.1; the reaction solution is stirred for at least 1 min before use; the plasma-treated gradient microarray porous silver nanopillars are immersed in the reaction solution for no more than 10 s, then slowly and uniformly pulled out over a period of at least 10 s, and dried in an air environment with a relative humidity of 60% to 70% for 15 to 30 min, and then cleaned, so that the polydimethylsiloxane-based hydrophobic molecular brush modification layer is distributed on the surface of the porous silver nanopillars and does not deposit between the porous silver nanopillars, so as to prevent affecting the sieving of plastic particles.
[0016] Preferably, the cleaning process specifically involves rinsing with deionized water and isopropanol in sequence.
[0017] This invention also provides a method for detecting the retention and separation of microplastics using the gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate, characterized by comprising the following steps: The gradient microarray porous nanosilver column / hydrophobic molecular brush composite SERS substrate is tilted, and the test liquid containing microplastic particles of different sizes is dropped into the upstream screening area. The tilted placement allows the test liquid to flow through no less than two screening areas by gravity, and open soft screening is performed by gravity drive. During open soft screening, microplastic particles of different sizes undergo differentiated retention, deceleration, enrichment, and / or contact in different screening zones; The gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate is dried. The hydrophobic effect of the polydimethylsiloxane-based hydrophobic molecular brush modification layer prevents the microplastics from being dragged to non-target areas by residual water during drying, thus preventing disordered aggregation. Different sieved areas after drying were used as different size retention detection areas, and SERS spectra were collected in the different size retention detection areas respectively; Identify the types of microplastic particles based on the position of characteristic peaks in the SERS spectrum.
[0018] Preferably, the test solution contains polystyrene microplastic particles with a particle size of 7 μm and polyethylene terephthalate microplastic particles with a particle size of 3 μm; the polystyrene microplastic particles with a particle size of 7 μm are subjected to SERS detection in a retention detection area with an edge spacing of 5 μm; the polyethylene terephthalate microplastic particles with a particle size of 3 μm are subjected to SERS detection in a retention detection area with an edge spacing of 2 μm.
[0019] Preferably, the tilting placement is specifically tilted at 5° relative to the horizontal plane. After the drop addition is completed, the gradient microarray porous nanosilver column / hydrophobic molecular brush composite SERS substrate is kept tilted until the test liquid has no obvious flow and is naturally dried in room temperature air environment.
[0020] Preferably, the SERS spectral acquisition conditions include: an excitation source wavelength of 532 nm, a laser power of 15 mW, an integration time of 5000 ms, and an objective lens magnification of 50×; the characteristic peaks of the polystyrene microplastic particles include 1001 cm⁻¹. -1 and 1602 cm -1 The identification characteristic peak of the polyethylene terephthalate microplastic particles includes 1615 cm⁻¹. -1 and 1728 cm -1 .
[0021] The polydimethylsiloxane-based hydrophobic molecular brush modification layer is formed by the hydrolysis and condensation reaction of dimethyldimethoxysilane under acid catalysis. It is applied to the surface of porous silver nanopillars as a surface modification, rather than filling the micron-sized gaps between adjacent porous silver nanopillars as a bulk polymer. Therefore, the hydrophobic molecular brush modification layer primarily alters the surface chemistry and wetting properties of the porous silver nanopillars without significantly reducing the effective interpillar spacing of the gradient array or the liquid flow space within the closed array.
[0022] The low surface energy groups on the surface of the hydrophobic molecular brush modification layer can increase the contact angle of the aqueous test liquid on the substrate surface. Under the same conditions such as pore size and liquid surface tension, the increased contact angle can reduce the capillary driving force for the aqueous test liquid to enter the nanopores on the surface of the porous silver nanopillars, the root of the pillars, and the narrow regions between the pillars, thereby reducing the excessive spreading, capillary retention, and residual liquid film of the test liquid in the microarray.
[0023] Reducing the amount of residual test liquid decreases the probability of microplastic particles continuously migrating to localized areas during the drying process and forming random particle clusters or particle bridging structures across adjacent micropillars in non-target locations. Simultaneously, because this invention employs an open micropillar array without a top cover, even if particle retention exists locally, the test liquid can still continue to flow through the paths between adjacent pillars and the open space around the particles. Therefore, the hydrophobic molecular brush modification layer reduces the risk of localized blockage caused by liquid residue and disordered particle accumulation, but does not eliminate the controlled deceleration, retention, and enrichment resulting from the dimensional relationship between the microplastic particle size and the pillar spacing.
[0024] It should be noted that the size retention separation described in this invention does not require the microplastic particles to be completely mechanically retained by the porous silver nanopillar array. Because this invention uses an open micropillar array without a top cap, the microplastic particles can still roll, slide, detour, or continue to migrate under the influence of the test liquid. The size retention separation described in this invention refers to the fact that microplastic particles of different sizes, when passing through porous silver nanopillar array regions with different spacings, exhibit differentiated residence times, enrichment levels, contact probabilities, or migration speeds due to differences in particle diameter, column spacing, local flow resistance, particle-surface contact probability, and particle movement paths, thereby forming differentiated detection regions in space that can be used for SERS detection.
[0025] The soft sieving process described in this invention is jointly controlled by the substrate tilt angle, the amount of sample to be tested, the sample loading position, the dropping method, the concentration of microplastic particles, and the drying method. Preferably, the SERS substrate is tilted at 5° relative to the horizontal plane, so that the 10 μm spacing region is located at the upstream high end, the 5 μm spacing region is located in the middle, and the 2 μm spacing region is located at the downstream low end. A total of 1.0 mL of sample to be tested is slowly added dropwise from the upstream end of the 10 μm spacing region, allowing the sample to flow sequentially through the 10 μm, 5 μm, and 2 μm spacing regions under the action of gravity and interfacial wetting.
[0026] When testing microplastic test solutions of different concentrations, the substrate tilt angle is maintained at 5°, and the sample loading volume, loading position, dropping method, and drying conditions are kept consistent, with only the concentration of microplastic particles in the test solution being changed. This ensures that the gravitational driving force, particle migration velocity, and regional residence conditions of the test solution remain essentially consistent under different concentration conditions, avoiding the comparability of test results for different concentrations caused by simultaneously changing the tilt angle.
[0027] After the addition is complete, keep the substrate at a 5° angle until there is no obvious liquid front moving on the substrate surface. Then, allow it to air dry naturally at room temperature until no visible liquid film is visible on the surface. After soft sieving, do not rinse, wipe, or purge the front of the array with strong airflow to reduce the possibility of secondary migration of retained particles.
[0028] Beneficial effects First, the present invention constructs a gradient microarray region with progressively decreasing spacing along the flow direction on the same highly conductive silicon wafer substrate, so that microplastic particles of different sizes undergo differentiated retention, deceleration, enrichment and contact during the flow process, thereby achieving the integration of size retention separation and SERS detection.
[0029] Second, the gradient microarray structure in this invention does not rely on deep holes or closed channels to rigidly trap particles, but rather controls the particle movement path, local residence time and contact probability by adjusting the micron-level array spacing, thereby reducing the risk of complete blockage.
[0030] Third, the present invention forms porous silver nanopillars by reducing Ag7O8NO3 precursor. The nanopores and nano-intervals in the porous silver nanopillars can form a large number of SERS hot spots, thereby improving the Raman detection sensitivity of microplastic particles.
[0031] Fourth, the polydimethylsiloxane-based hydrophobic molecular brush modification layer in this invention covers the surface of the porous silver nanopillars in the form of a thin surface layer, without filling the gaps between adjacent micropillars in the form of a bulk polymer, thus essentially maintaining the micron-scale open flow space between the pillars. This modification layer can regulate the wetting and spreading behavior of the aqueous test solution on the surface of the porous silver nanopillars, providing interface control for the directional transport of the test solution on the gradient array and the contact between the microplastic particles and the SERS active surface.
[0032] Fifth, this invention can be used for the mixed detection of microplastic particles of different sizes and materials. For example, when the test liquid flows from the 10 μm spacing region to the 5 μm and 2 μm spacing regions, 7 μm polystyrene microplastic particles can be retained in the 5 μm region and detected by SERS, and 3 μm polyethylene terephthalate microplastic particles can be retained in the 2 μm region and detected by SERS. Attached Figure Description
[0033] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0035] Figure 1 This is a schematic diagram of the preparation process of the gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate of the present invention.
[0036] Figure 2 This is a schematic diagram of the gradient array region and the microplastic size retention and separation planar structure described in this invention.
[0037] Figure 3 These are scanning electron microscope (SEM) images of the products of each stage of the gradient microarray of the present invention; (a), (b), and (c) are top-view SEM images of the microarray spacing of 10 μm, 5 μm, and 2 μm after electrochemical growth of Ag7O8NO3 and removal of residual negative photoresist, respectively; (d), (e), and (f) are 45° tilted SEM images of the porous silver nanoarray spacing of 10 μm, 5 μm, and 2 μm after sodium borohydride reduction, respectively; (g) is a local high-magnification SEM image of the Ag7O8NO3 precursor; and (h) is a local high-magnification SEM image of the reduced porous silver nanopillars, showing abundant nanoscale pore structures. Figure 4 The images show a comparison of the contact angles of the substrate surface before and after modification with a polydimethylsiloxane-based hydrophobic molecular brush; where (a) is a photograph of the contact angle before modification and (b) is a photograph of the contact angle after modification. Figure 5 A comparison of the Raman signal intensities of the Ag7O8NO3 precursor and the nanoporous silver p-4-mercaptobenzoic acid (4-MBA) probe molecule; Figure 6 The images show the distribution of microplastic particles in different spacing regions after gradient microarray soft sieving and natural drying when the final mass concentration of 7 μm PS microspheres and 3 μm PET microspheres in the mixed test solution is 0.1 μg / mL. Among them, (a) is the 10 μm spacing region, (b) is the 5 μm spacing region, and (c) is the 2 μm spacing region.
[0038] Figure 7 This image shows the detection results of 3 μm polyethylene terephthalate (PET) microspheres with different final mass concentrations in a mixed test solution using the SERS substrate of this invention. The SERS spectra were acquired in a small-spacing region with a distance of 2 μm between the edges of adjacent porous silver nanopillars. The characteristic peak for identifying PET microspheres is located at 1615 cm⁻¹. -1 and 1728 cm -1 In the figure, 0, 0.1, 0.3, 1, 3 and 10 μg / mL represent the final mass concentration of PET microspheres in the mixed test solution.
[0039] Figure 8This is a graph showing the detection results of 7 μm polystyrene (PS) microspheres with different final mass concentrations in a mixed test solution using the SERS substrate of this invention. The SERS spectrum was acquired in the mid-spacing region where the edge spacing between adjacent porous silver nanopillars is 5 μm. The characteristic peak for PS microsphere identification is located at 1001 cm⁻¹. -1 and 1602 cm -1 In the figure, 0, 0.1, 0.3, 1, 3 and 10 μg / mL represent the final mass concentration of PS microspheres in the mixed test solution. Detailed Implementation
[0040] This invention constructs an open micropillar array structure with a gradient decreasing along the flow direction. Utilizing the size matching relationship between the microplastic particle size and the inter-pillar edge spacing, it achieves "soft sieving" of particles of different sizes. Compared to traditional rigid retention, this open structure allows liquid to circulate, fundamentally avoiding the risk of channel blockage. This invention, by limiting the formation of porous silver nanopillars from the reduction of Ag7O8NO3 precursor, constructs abundant nanopores, nano-intervals, and particle connection structures in situ on the surface of the micron-scale pillars. Simultaneously, a high-density SERS electromagnetic field "hot spot" is formed at the physical sieving site, achieving in-situ integration of "sieving and detection." This invention controls the hydrolysis and condensation of dimethyldimethoxysilane on the surface of a silver column under specific acid catalysis and humidity conditions, forming a polydimethylsiloxane-based hydrophobic molecular brush modification layer distributed only on the column surface. This modification layer not only increases the surface contact angle, but more importantly, by regulating the capillary driving force, it effectively suppresses the drag force of the residual liquid film on microplastic particles during the drying process, preventing disordered aggregation of particles in non-target areas, thereby ensuring the stability of size separation and the accuracy of SERS detection. The gradient array structure, porous nano-silver SERS active sites, and surface hydrophobic molecular brushes support each other and synergistically solve the technical problems of "difficult separation, easy clogging, weak signal, and easy drift" in microplastic detection.
[0041] The technical solution of the present invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not intended to limit the scope of protection of the present invention. All equivalent substitutions, conventional modifications or parameter adjustments made based on the technical concept of the present invention should fall within the scope of protection of the present invention.
[0042] Example 1: Preparation of gradient microarray Ag7O8NO3 precursor structure First, a P-type high-conductivity silicon wafer with a resistivity of 0.0005–0.0009 Ω·cm was selected as the conductive substrate. After cleaning and drying, the P-type high-conductivity silicon wafer was coated with RZJ-390PG-30 negative photoresist. The negative photoresist was spin-coated at 6000 rpm for 60 s, followed by pre-baking at 120 °C for 2 min. The negative photoresist was patterned using a laser direct-write device. After exposure, no post-baking was performed. The wafer was developed with ZX-238 developer for 40 s and rinsed with deionized water for 30 s, forming a circular opening array region with different edge spacing in the negative photoresist layer. The circular openings exposed the surface of the P-type high-conductivity silicon wafer.
[0043] The circular opening array comprises three regions: a large-spacing region, a medium-spacing region, and a small-spacing region. The diameter of the circular openings in all three regions is 4 μm, and the edge spacing between adjacent circular openings is 10 μm, 5 μm, and 2 μm, respectively. The corresponding center-to-center distances between adjacent circular openings are 14 μm, 9 μm, and 6 μm, respectively.
[0044] A three-electrode electrochemical system was constructed using a P-type high-conductivity silicon wafer with the circular opening array region as the working electrode, a carbon rod as the counter electrode, and a saturated Ag / AgCl electrode as the reference electrode. The working electrode was placed in an electrolyte containing 0.16 M silver nitrate and 0.6 M boric acid, and electrochemical growth was performed for 120 s at 2.0 V (vs. saturated Ag / AgCl) to allow the Ag7O8NO3 precursor to grow in situ on the surface of the high-conductivity silicon wafer exposed within the circular openings.
[0045] After electrochemical growth, acetone was used to remove the remaining negative photoresist around the circular openings, resulting in a gradient microarray Ag7O8NO3 precursor columnar structure defined by the negative photoresist circular opening array template. X-ray diffraction was used to confirm the phase composition of the obtained precursor, confirming it as Ag7O8NO3. The morphology of the obtained Ag7O8NO3 precursor columnar structure is shown below. Figure 3 (a) to (c) and Figure 3 As shown in (g).
[0046] Example 2: Preparation of Gradient Microarray Porous Silver Nanopillars The gradient microarray Ag7O8NO3 precursor columnar structure prepared in Example 1 was immersed in 500 mM sodium borohydride solution for 10 min to allow the Ag7O8NO3 precursor to undergo a reduction reaction and transform into gradient microarray porous silver nanopillars. After the reduction treatment, the sample was gently rinsed with ultrapure water to remove residual reactants.
[0047] The resulting gradient microarray porous silver nanopillars retain the micrometer-scale columnar array structure with varying spacings defined by a circular open array template of negative photoresist, while simultaneously forming nanopores, nano-gap structures, and / or nanoparticle interconnections on the surface and / or inside the porous silver nanopillars. These nanostructures can provide localized electromagnetic field enhancement regions to enhance the Raman signal of the microplastic particles under test. The morphology of the resulting porous silver nanopillar structure is as follows: Figure 3 (d)~(f) and Figure 3 As shown in (h).
[0048] Example 3: Preparation of a polydimethylsiloxane-based hydrophobic molecular brush modified layer The gradient microarray porous silver nanopillars prepared in Example 2 were subjected to oxygen plasma treatment with a plasma power of 70 W and a treatment time of 30 s to improve the surface reactivity of the substrate and reduce the influence of airborne organic pollutants on subsequent reactions.
[0049] Prepare the hydrophobic molecular brush reaction solution. Specifically, mix 10 g of isopropanol, 1 g of dimethyldimethoxysilane, and 0.1 g of concentrated sulfuric acid, and stir for about 1 min to obtain the reaction solution. The reaction solution is preferably used within 30 min of preparation.
[0050] The gradient microarray porous silver nanopillars, treated with oxygen plasma, were immersed in the reaction solution for approximately 10 seconds, and then slowly pulled out. Excess reaction solution was gently wiped from the back of the sample using filter paper, and the sample was placed in a fume hood and dried in an air environment at approximately 21 °C and 60%–70% relative humidity for 15–30 minutes. Under these humidity conditions, ambient moisture participates in the acid-catalyzed hydrolysis and subsequent condensation of dimethyldimethoxysilane, thereby forming a polydimethylsiloxane-based hydrophobic molecular brush modification layer on the surface of the porous silver nanopillars.
[0051] After the reaction was completed, the sample was rinsed with deionized water and isopropanol in sequence, and then dried in a fume hood to obtain a gradient microarray porous nanosilver column / hydrophobic molecular brush composite SERS substrate.
[0052] The process and parameters in this step work together to enable dimethyldimethoxysilane to undergo surface grafting hydrolysis and condensation on the surface of the silver column, forming a nanoscale molecular brush, rather than accumulating into bulk PDMS in the intercolumn voids.
[0053] Specifically, the following four control points work together: Control point 1: Oxygen plasma pretreatment (70W, 30s) This step is called "activating surface reactivity". Plasma treatment introduces active sites such as –OH groups on the surface of porous silver nanopillars, enabling DMDMS to preferentially undergo silanization grafting reactions with the silver nanopillar surface. The reaction occurs "on the surface of the silver nanopillar with active sites", not "in the pores" - because there are no active surfaces available for grafting in the pores, where DMDMS will only make brief contact and then be carried away by lifting and rinsing.
[0054] Control point two: Control the immersion time to 10 seconds and slowly lift the object. This step is the core parameter for controlling film thickness. 10-second immersion: DMDMS has just begun hydrolysis and condensation under acid catalysis and has not yet formed a large amount of high molecular weight polymer. Dimethyldimethoxysilane is a bifunctional short-chain alkoxysilane, which hydrolyzes in water to silanol and then condenses. This process is only enough to graft a nanoscale molecular brush thin layer onto the surface within 10 seconds.
[0055] Slow lifting: Allow the reaction solution to detach evenly from the surface, avoiding capillary accumulation in the intercolumn gaps due to rapid extraction.
[0056] If the immersion time is extended to several minutes or longer, DMDMS will self-condense into high molecular weight PDMS prepolymer in the solution phase, and the bulk PDMS will be carried into the inter-column voids during the pull-out process.
[0057] Control point 3: Air drying at specific humidity levels (RH 60–70% at room temperature, 15–30 min) In this step, ambient moisture plays a dual role: as a co-reactant, participating in the acid-catalyzed hydrolysis of DMDMS (DMDMS + H2O → silanol → condensation grafting to the surface), and controlling the reaction rate: 60–70% RH provides an appropriate amount of ambient water, ensuring the hydrolysis reaction proceeds while avoiding excessive moisture that could cause DMDMS to polymerize rapidly in the liquid phase.
[0058] If the humidity is too low, hydrolysis will be incomplete, the grafting density will be insufficient, and the hydrophobic effect will be poor. If the humidity is too high, DMDMS will self-polymerize in large quantities in the solution phase, and bulk PDMS will easily remain in the column during the pull-out process. Limiting the RH to 60–70% is precisely to lock the reaction within a window where surface grafting is the primary process.
[0059] Control Point 4: Rinse with deionized water and isopropanol This step is to "remove ungrafted prepolymers". Even if a small amount of DMDMS begins to condense in the solution phase, the rinsing step will wash away these ungrafted polymers, leaving only the molecular brush layer covalently grafted onto the silver column surface via Si–O–Ag or Si–O–Si chemical bonds.
[0060] The static water contact angle of the substrate before and after modification was measured using ultrapure water, with each water droplet volume being 15 μL. For example... Figure 4 As shown, compared with the unmodified substrate, the water contact angle of the substrate surface modified with polydimethylsiloxane-based hydrophobic molecular brushes increased, indicating that the modified layer can reduce the wettability of the porous silver nanopillar surface. The modified layer was formed on the porous silver nanopillar surface through short-time immersion, slow lifting, air drying, and subsequent rinsing, rather than filling the 2–10 μm interpillar gaps in the form of a bulk polymer. Therefore, it mainly alters the interfacial wettability of the substrate surface without significantly changing the effective interpillar spacing and open flow space of the micropillar array.
[0061] With an increased water contact angle, the capillary driving force for the aqueous test solution to enter the nanopores on the surface of the porous silver nanopillars, the root of the pillars, and the narrow regions between the pillars is weakened. This helps to reduce excessive spreading, capillary retention, and residual liquid film of the test solution in the array. This reduces the probability of microplastic particles continuously accumulating in localized locations with residual liquid during the drying process, forming particle clusters or bridging structures across adjacent micropillars. Therefore, the hydrophobic molecular brush modification layer can interfacially regulate the wetting, spreading, and residual behavior of the aqueous test solution while essentially maintaining the open flow space of the gradient microarray. This effect does not exclude all microplastic particles; microplastic particles can still undergo controlled deceleration, retention, and enrichment in the corresponding gradient regions according to the relationship between their particle size and the interpillar spacing.
[0062] Example 4: Comparative Test of SERS Enhancement Performance Based on 4-Mercaptobenzoic Acid (4-MBA) Using 4-MBA as the probe molecule, Raman signal intensity was compared between Ag7O8NO3 precursor substrate and nanoporous silver substrate reduced with sodium borohydride.
[0063] Specifically, 4-MBA was adsorbed onto the surfaces of an Ag7O8NO3 precursor substrate and a nanoporous silver substrate, and their Raman spectra were collected under the same Raman testing conditions. By comparing the Raman signal intensity of the characteristic peak of 4-MBA, the effect of Ag7O8NO3 reduction to form nanoporous silver on the SERS enhancement performance was evaluated.
[0064] Test results are as follows Figure 5 As shown, compared to the Ag7O8NO3 precursor substrate, the nanoporous silver substrate formed after sodium borohydride reduction exhibits a stronger 4-MBA Raman characteristic signal. This indicates that the nanoporous silver structure formed after reduction treatment can provide more local electromagnetic field enhancement regions such as nanopores and nano-intervals, thereby improving the SERS enhancement capability of the substrate. This result demonstrates that the Ag7O8NO3 precursor, after reduction to nanoporous silver, can serve as an effective enhancement structure for SERS detection in microplastics in this invention.
[0065] Example 5: Size retention separation-SERS detection of 7 μm PS and 3 μm PET mixed microplastics Aqueous suspensions containing polystyrene (PS) microspheres with a particle size of 7 μm and polyethylene terephthalate (PET) microspheres with a particle size of 3 μm were prepared separately, and the two suspensions were mixed to obtain a PS / PET mixed test solution. Five groups of mixed test solutions containing microplastic particles were prepared, in which the final mass concentrations of PS microspheres and PET microspheres after mixing were 0.1 μg / mL, 0.3 μg / mL, 1 μg / mL, 3 μg / mL, and 10 μg / mL, respectively; at the same time, a blank control test solution without PS microspheres and PET microspheres was prepared, denoted as the 0 μg / mL group. That is, in each concentration group containing microplastic particles, the final mass concentrations of PS microspheres and PET microspheres were the same, and the mass concentration ratio of the two was 1:1. The mixed test solutions were gently mixed before use to ensure that the PS microspheres and PET microspheres were uniformly dispersed.
[0066] The gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate obtained in Example 3 was placed on an inclined stage, so that the substrate surface formed a 5° angle with the horizontal plane. Among them, the 10 μm spacing region was located at the upstream high end, the 5 μm spacing region was located in the middle, and the 2 μm spacing region was located at the downstream low end. The length direction of the substrate was consistent with the preset flow direction of the test liquid.
[0067] Using a pipette, slowly add 1.0 mL of the mixed test solution from the upstream end of the 10 μm spacing region. During the addition process, keep the substrate tilt angle and sample loading position constant, allowing the test solution to flow sequentially through the 10 μm spacing region, the 5 μm spacing region, and the 2 μm spacing region to avoid significant liquid flow impact, lateral overflow, and disordered particle accumulation caused by rapid sample loading.
[0068] When testing mixed test solutions of different concentrations, the substrate tilt angle was fixed at 5°, the total sample loading volume was 1.0 mL, and the loading position, dropping method and subsequent drying conditions were kept consistent. Only the final mass concentration of PS microspheres and PET microspheres in the mixed test solution was changed synchronously.
[0069] After the addition is complete, keep the substrate at a 5° angle until no more noticeable liquid fronts appear on the substrate surface. Then, allow the substrate to air dry at room temperature until no visible liquid film remains on the surface. After soft sieving and drying, do not rinse, wipe, or purge the array front surface with strong airflow to avoid secondary migration of microplastic particles already stationary in different spacing areas.
[0070] During the flow of the test liquid, the 7 μm PS microspheres can continue to migrate downstream through the 10 μm spacing region. When they enter the 5 μm spacing region, because the particle size is larger than the 5 μm edge spacing of the adjacent porous silver nanopillars, the probability of the particles passing through directly decreases, while the detour distance, the probability of contact between the particles and the micropillars, and the residence time in the region increase. Therefore, deceleration and enrichment preferentially occur in the 5 μm spacing region, especially at the end near the 2 μm spacing region.
[0071] 3 μm PET microspheres, with a particle size smaller than the 5 μm inter-column edge spacing, are more likely to pass through the 5 μm spacing region and continue downstream compared to 7 μm PS microspheres. When they enter the 2 μm spacing region, their passage probability decreases because the particle size is larger than the 2 μm inter-column edge spacing, and they decelerate, remain stationary, and accumulate in the 2 μm spacing region.
[0072] The size retention separation described herein does not require complete mechanical retention of PS microspheres and PET microspheres in their respective regions. Instead, it utilizes the relative relationship between the microplastic particle size and the edge spacing of the porous silver nanopillars to induce different passage probabilities, migration velocities, residence times, and regional enrichment levels for particles of different sizes, thereby achieving soft sieving and spatially zoned detection. In this invention, each silver pillar serves as both a carrier of SERS hotspots and a physical barrier for size sieving, enabling in-situ separation and detection.
[0073] After soft sieving and natural drying, scanning electron microscopy was used to observe samples with a final mass concentration of 0.1 μg / mL for both PS and PET microspheres in the mixed test solution. The distribution of microplastic particles in the 10 μm, 5 μm, and 2 μm spacing regions was recorded. The results are as follows: Figure 6 As shown, the overall number of microplastic particles remaining in the 10 μm spacing region is relatively small, indicating that 7 μm PS microspheres and 3 μm PET microspheres have a high probability of continued migration in this region. A large number of PS microspheres with a diameter of approximately 7 μm are observed in the 5 μm spacing region, indicating that the probability of PS microspheres passing directly through this region is reduced, and they undergo preferential deceleration, residence, and enrichment. A large number of PET microspheres with a diameter of approximately 3 μm are observed in the 2 μm spacing region, indicating that after passing through the 5 μm spacing region, PET microspheres undergo preferential deceleration, residence, and enrichment in the 2 μm spacing region.
[0074] This application integrates "size separation" and "SERS detection" into the same process on the same substrate, using an open micropillar array instead of a closed channel. By varying the relative relationship between particle size and the spacing between the silver pillars, it generates differentiated throughput probabilities, migration speeds, and residence times, enabling soft sieving. This invention adjusts the wettability of the silver pillar surface to prevent microplastics from being dragged away by residual water, while essentially maintaining an open flow space between the pillars, forming a synergistic relationship: hydrophobic modification reduces "disorderly accumulation and clogging," while the open array ensures "orderly soft sieving," with both functions mutually supporting each other.
[0075] A small number of particles of other sizes were still observed in different spacing regions, indicating that the present invention achieves soft sieving based on differences in particle passage probability, migration speed, and residence time, rather than complete mechanical interception of the two types of microplastic particles. Furthermore, although particle aggregation was observed in localized areas, most of the porous silver nanopillars remained open, and no continuous particle blockage covering the entire observation area was observed.
[0076] A 532 nm laser was used as the excitation source with a laser power of 15 mW, an integration time of 5000 ms, and an objective lens magnification of 50×. SERS spectra were collected from regions with different spacing.
[0077] Test results as follows Figure 7 and Figure 8 As shown. Figure 7 SERS spectra of 3 μm PET microspheres with different final mass concentrations were collected in a 2 μm spacing region. PET at 1615 cm⁻¹ was observed. -1 and 1728 cm -1 Characteristic peaks at the location; Figure 8 SERS spectra of 7 μm PS microspheres with different final mass concentrations were collected in a 5 μm spacing region. PS was observed at 1001 cm⁻¹. -1 and 1602cm -1 The characteristic peaks at the specified locations are shown in the figure. Each concentration in the figure represents the final mass concentration of the corresponding microplastic particles in the mixed test solution.
[0078] The test results show that the gradient microarray porous nanosilver column / hydrophobic molecular brush composite SERS substrate of the present invention can achieve size retention separation and SERS recognition detection of microplastic particles of different sizes and materials.
[0079] See Figure 6 Experimental data show that when the test liquid flows through the gradient array described in this invention, 7 μm PS microspheres are mainly enriched in the 5 μm spacing region, and 3 μm PET microspheres are mainly enriched in the 2 μm spacing region, demonstrating the effectiveness of soft sieving. See also... Figure 7 , Figure 8The SERS spectral analysis results clearly identified the characteristic peaks of the two microplastics even at an extremely low concentration of 0.1 μg / mL, verifying the extremely high sensitivity of the SERS hotspots provided by the porous silver nanopillars. Comparative scanning electron microscopy revealed that the hydrophobic molecular brush-modified substrate, prepared by drying under specific humidity conditions (S6) and subsequent rinsing according to this invention, maintained unobstructed micron-level gaps between the pillars, with no bulk polymer filling observed. Furthermore, the dried microplastic particles did not exhibit significant cross-pillar bridging or random aggregation. In contrast, the control samples without hydrophobic modification or those prepared using conventional spin-coating methods generally showed a large number of particles being dragged to the edges or agglomerated after drying, making accurate localization and detection impossible. This result demonstrates the crucial role of the surface molecular brush modification strategy described in this invention in maintaining open flow space and stable separation, producing unexpected technical effects.
Claims
1. A gradient microarray porous nanosilver column / hydrophobic molecular brush composite SERS substrate for the detection of microplastic size retention separation, characterized in that, include: A conductive substrate, wherein an array of porous silver nanopillars is disposed on the surface of the conductive substrate as a gradient microarray porous silver nanopillar layer. The porous silver nanopillars are coated with a polydimethylsiloxane-based hydrophobic molecular brush modification layer. According to the preset flow direction of the test liquid, the gradient microarray porous silver nanoparticle layer is divided into several sieving regions. Within the same sieving region, the spacing between the porous silver nanoparticles is the same. Between adjacent sieving regions, the spacing between the porous silver nanoparticles upstream is greater than that downstream. The diameter of the porous silver nanopillars is 1–10 μm, and the spacing between adjacent porous silver nanopillars is 1–20 μm.
2. The gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate according to claim 1, characterized in that, The spacing between the porous silver nanoparticles is specifically the edge spacing between any two adjacent porous silver nanoparticles within the same sieving area. The sieving region consists of three areas: a large-spacing region, a medium-spacing region, and a small-spacing region. The edge spacing between adjacent porous silver nanopillars in the large-spacing region is 6–15 μm; the edge spacing between adjacent porous silver nanopillars in the medium-spacing region is 3–8 μm; and the edge spacing between adjacent porous silver nanopillars in the small-spacing region is 1–4 μm.
3. The gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate according to claim 2, characterized in that, The edge spacing between adjacent porous silver nanopillars in the large-spacing region is 10 μm; the edge spacing between adjacent porous silver nanopillars in the medium-spacing region is 5 μm; and the edge spacing between adjacent porous silver nanopillars in the small-spacing region is 2 μm.
4. The method for preparing the gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate according to claim 1, characterized in that, Includes the following steps: S1, a highly conductive silicon wafer is provided as a conductive substrate, and a negative photoresist is coated on the surface of the conductive substrate; S2, The negative photoresist is patterned using a laser direct writing process to form a circular opening array region with different edge spacing in the negative photoresist layer, so that the highly conductive silicon wafer is exposed at the circular openings. S3, using a highly conductive silicon wafer with the circular opening array region as the working electrode, electrochemical growth is carried out in a silver-containing electrolyte to grow the Ag7O8NO3 precursor on the surface of the highly conductive silicon wafer exposed in the circular opening. S4, remove the negative photoresist to obtain a gradient microarray Ag7O8NO3 precursor columnar structure defined by the circular opening array template; S5, the gradient microarray Ag7O8NO3 precursor columnar structure is placed in a reducing agent solution for reduction treatment, so that the Ag7O8NO3 precursor is transformed into gradient microarray porous silver nanopillars. S6, a polydimethylsiloxane-based hydrophobic molecular brush modification layer is formed on the surface of the gradient microarray porous silver nanopillars to obtain the gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate.
5. The method according to claim 4, characterized in that, In step S6, the method for forming the polydimethylsiloxane-based hydrophobic molecular brush modification layer includes: The gradient microarray porous silver nanopillars were subjected to plasma treatment. The plasma-treated gradient microarray porous silver nanopillars were brought into contact with a reaction solution containing dimethyldimethoxysilane, isopropanol and concentrated sulfuric acid. Dimethyldimethoxysilane undergoes a hydrolysis-condensation reaction on the surface of the gradient microarray porous silver nanopillars under acid catalysis and with the participation of ambient moisture, forming a polydimethylsiloxane-based hydrophobic molecular brush modification layer.
6. The method according to claim 5, characterized in that, The mass ratio of isopropanol, dimethyldimethoxysilane, and concentrated sulfuric acid in the reaction solution is 10:1:0.
1. The reaction solution is stirred for at least 1 min before use. The plasma-treated gradient microarray porous silver nanopillars are immersed in the reaction solution for no more than 10 s, and then slowly and uniformly pulled out over a period of at least 10 s. They are then dried in an air environment with a relative humidity of 60%–70% for 15–30 min, and then cleaned to ensure that the polydimethylsiloxane-based hydrophobic molecular brush modification layer is distributed on the surface of the porous silver nanopillars and does not deposit between the porous silver nanopillars, so as to prevent affecting the sieving of plastic particles.
7. The method according to claim 6, characterized in that, The cleaning process specifically involves rinsing with deionized water and isopropanol in sequence.
8. A method for detecting the retention and separation of microplastics using the gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate as described in claim 1, characterized in that, Includes the following steps: The gradient microarray porous nanosilver column / hydrophobic molecular brush composite SERS substrate is tilted, and the test liquid containing microplastic particles of different sizes is dropped into the upstream screening area. The tilted placement allows the test liquid to flow through no less than two screening areas by gravity, and open soft screening is performed by gravity drive. During open soft screening, microplastic particles of different sizes undergo differentiated retention, deceleration, enrichment, and / or contact in different screening zones; The gradient microarray porous silver nanopillar / hydrophobic molecular brush composite SERS substrate is dried. The hydrophobic effect of the polydimethylsiloxane-based hydrophobic molecular brush modification layer prevents the microplastics from being dragged to non-target areas by residual water during drying, thus preventing disordered aggregation. Different sieved areas after drying were used as different size retention detection areas, and SERS spectra were collected in the different size retention detection areas respectively; Identify the types of microplastic particles based on the position of characteristic peaks in the SERS spectrum.
9. The method according to claim 8, characterized in that, The test solution contains polystyrene microplastic particles with a particle size of 7 μm and polyethylene terephthalate microplastic particles with a particle size of 3 μm; the polystyrene microplastic particles with a particle size of 7 μm are subjected to SERS detection in a retention detection area with an edge spacing of 5 μm; the polyethylene terephthalate microplastic particles with a particle size of 3 μm are subjected to SERS detection in a retention detection area with an edge spacing of 2 μm.
10. The method according to claim 8 or 9, characterized in that, The tilting placement is specifically a 5° tilt relative to the horizontal plane. After the drop addition is completed, the gradient microarray porous nanosilver column / hydrophobic molecular brush composite SERS substrate is kept tilted until the test liquid has no obvious flow and is naturally dried in a room temperature air environment.